PENERAPAN AROMATERAPI LEMON UNTUK MENURUNKAN INTENSITAS NYERI PADA PASIEN POST OPERASI LAPARATOMI DI RUANG HCU RSUD KARAWANG - Grace Evelyn; Dina Hartini (Ensiklopedia Education Review, 2023)
Surgery or surgery is any action that uses invasive methods to diagnose, treat Surgery or surgery is any action that uses invasive methods to diagnose, treat disease, injury or deformity of the body, generally carried out by making incisions that can cause physiological changes in the body and affect other organs of the body (Scholz et al., 2019). Knowing the application of lemon aromatherapy to reduce pain intensity in postoperative laparotomy patients in the HCU room of Karawang Hospital. The research design used by the researcher was a Quasy Experiment with a pre-post test design. This study used a sample of 40 respondents who underwent Lemon Aromatherapy intervention. The sampling technique used is Non Probability Sampling. The results of the analysis using the Paired t-test showed that the p-value of blood sugar levels was 0.001 (p-value <0.05). It can be concluded that there is an effect of lemon aromatherapy on reducing the pain scale in post-op laparotomy patients. The results show that lemon aromatherapy can reduce pain intensity in post op laparotomy patients.